Metabolic Effects of Antiretroviral Therapy in Women living with HIV/AIDS (Research, Society and Development, 2022)
Cultural inequalities that are harmful to women can potentialize the risk of HIV in this group. The aim of this research was to draw the epidemiological and metabolic profile of women diagnosed with HIV. It consists in a cross-sectional analysis of a cohort study, performed in women living with HIV/AIDS that received antiretroviral therapy (ARV) and that were users of the Specialized Care Service in the municipality of Ponta Grossa – PR, between 2003 and 2018. The analysis was descriptive and the association between the medicines used and the metabolic changes were evaluated with relative risk (RR) and through the chi-squared test. Medical records of 451 women were analyzed: 80,5% were white, 44,4% were married, 88,2% contracted HIV by sexual transmission and 83,1% were heterosexual. There was significant association as a risk factor between the use of Protease Inhibitors (PI) and alterations on HDL cholesterol (RR = 1,70, IC95% 1,32-2,20 and p